2005
DOI: 10.1089/hum.2005.16.1175
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Bystander Effect of Somatostatin Receptor sst2 AfterIn VivoGene Transfer into Human Pancreatic Cancer Cells

Abstract: Pancreatic cancer is one of the most aggressive and devastating human malignancies. The present study was conducted to determine whether in vivo sst2 gene transfer into human pancreatic tumors would impair tumor progression, and to characterize sst2 antitumoral bystander mechanisms. sst2 administration, using the synthetic vector PEI, strongly inhibited tumor progression of human pancreatic adenocarcinoma, in vivo. sst2 gene transfer induced intratumoral production of its ligand somatostatin. Disruption of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 70 publications
2
37
0
Order By: Relevance
“…Preclinical studies conducted in pancreatic adenocarcinoma animal models demonstrated that intratumoral sst2 gene transfer (using polyethylenimine synthetic vector) caused inhibition of intratumoral production of somatostatin that was critical for the sst2 antitumoral effect. As a consequence, primary tumor growth and angiogenesis were highly decreased and associated with a reduction in microvessel density, inhibition of intratumoral production of VEGF and up-regulation of anti-angiogenic sst3 receptor expression in peripheral tumor vessels (Vernejoul et al, 2002;Carrere et al, 2005). When co-injected with sst2 vector, small interfering RNA targeting somatostatin mRNA completely blocked somatostatin production in tumors and antagonized sst2-mediated antitumoral and antiangiogenic effects (Carrere et al;2005).…”
Section: Novel Anti-tumor Therapy Based On Sst2 Gene Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical studies conducted in pancreatic adenocarcinoma animal models demonstrated that intratumoral sst2 gene transfer (using polyethylenimine synthetic vector) caused inhibition of intratumoral production of somatostatin that was critical for the sst2 antitumoral effect. As a consequence, primary tumor growth and angiogenesis were highly decreased and associated with a reduction in microvessel density, inhibition of intratumoral production of VEGF and up-regulation of anti-angiogenic sst3 receptor expression in peripheral tumor vessels (Vernejoul et al, 2002;Carrere et al, 2005). When co-injected with sst2 vector, small interfering RNA targeting somatostatin mRNA completely blocked somatostatin production in tumors and antagonized sst2-mediated antitumoral and antiangiogenic effects (Carrere et al;2005).…”
Section: Novel Anti-tumor Therapy Based On Sst2 Gene Transfermentioning
confidence: 99%
“…As a consequence, primary tumor growth and angiogenesis were highly decreased and associated with a reduction in microvessel density, inhibition of intratumoral production of VEGF and up-regulation of anti-angiogenic sst3 receptor expression in peripheral tumor vessels (Vernejoul et al, 2002;Carrere et al, 2005). When co-injected with sst2 vector, small interfering RNA targeting somatostatin mRNA completely blocked somatostatin production in tumors and antagonized sst2-mediated antitumoral and antiangiogenic effects (Carrere et al;2005). Based on the anti-tumor properties of sst2, we have proposed a phase I clinical trial aimed at rendering human pancreatic adenocarcinomas more sensitive to the cytotoxic action of the chemotherapeutic compound Gemcitabine (GEMZAR TM ).…”
Section: Novel Anti-tumor Therapy Based On Sst2 Gene Transfermentioning
confidence: 99%
“…[29][30][31] Other gene delivery systems, such as complexed DNA (PEI), adenovirus and SV40-derived vectors showed poor efficiencies or transient expression of the transgene, respectively. 8,9 Lentiviral vectors were developed to overcome these limitations. The lentiviral vector-mediated gene therapy has great promise in cancer treatment, because of its long-term expression and high efficiency in transducing dividing and nondividing cells, including the chemoresistant population located in the hypoxic cores of tumors.…”
Section: Lentiviral Vectors For Pc Therapy E Ravet Et Almentioning
confidence: 99%
“…In this study, lentiviral-based vectors surpass nonviral vectors (PEI), adenoviral or SV40-based vectors in their ability to transduce PC-derived cells. 8,9 Understanding the molecular basis of PC has provided a wide range of potential intracellular targets for gene therapy approaches. 36 Targeting PC by molecular abnormality remains elusive because of the accumulation of multiple genetic changes during its multistep carcinogenesis.…”
Section: Lentiviral Vectors For Pc Therapy E Ravet Et Almentioning
confidence: 99%
See 1 more Smart Citation